Potassium sodium niobate ceramic-based wound healing promoting film and preparation method thereof

The KNN-PVDF composite film prepared by ball milling and casting method solves the problem of expensive equipment and difficult to remove by-products in traditional methods, realizes efficient soft tissue defect repair, and provides excellent biocompatibility and piezoelectric performance. Treatment plan.

CN119303163APending Publication Date: 2025-01-14CENT SOUTH UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411428972.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-14
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

In the prior art, when using composite films to treat large-area soft tissue defects, the local drug effect concentration is low, the material bioactivity is insufficient, and the traditional preparation methods have problems such as expensive equipment and difficult to remove toxic by-products, which is difficult to effectively promote the repair of soft tissue.

Method used

Potassium sodium niobate ceramic-based precursor powder was synthesized by ball milling method, and KNN-PVDF composite film was prepared by combining casting method and ultrasonic dispersion technology. Anhydrous ethanol and N,N-dimethylformamide solution were mixed and dried to form a Composite film with excellent piezoelectric properties and biocompatibility.

Benefits of technology

A customized composite film is realized, which improves piezoelectric properties and biocompatibility, promotes the migration of fibroblasts and wound healing, and provides a new theoretical basis for the repair of large-area soft tissue defects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119303163A_ABST
    Figure CN119303163A_ABST
Patent Text Reader

Abstract

The invention provides a potassium-sodium niobate ceramic-based wound healing promoting film and a preparation method thereof. The composite film material is prepared from polyvinylidene fluoride-trifluoroethylene and potassium-sodium niobate composite powder. The prepared composite film is high in biological activity and good in wound recovery promoting performance. The problem that the large-area skin defect is difficult to recover can be solved, and a new theoretical basis is provided for treating the large-area skin defect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of preparing piezoelectric films by a casting method, and in particular to an enhanced composite film material with a piezoelectric effect and a preparation method thereof. Background Art

[0002] The difficulty in repairing large-area soft tissue defects is the key to chronic and refractory wounds. Long-term ischemia and hypoxia in the central area of ​​large-area soft tissue defects can easily cause infection in the skin defect area and significantly prolong the wound healing time. Subsequent treatment and clinical management have brought huge burdens to patients and society. At present, the main methods commonly used in clinical practice to repair refractory wounds are the application of traditional dressings, surgical debridement, and the use of growth factor drugs. However, these treatment methods have disadvantages such as low local drug concentration, insufficient material bioactivity, and secondary trauma. Polyvinylidene fluoride (PVDF) is one of the biomedical materials approved by the Food and Drug Administration, with good bioactivity, biocompatibility and mechanical properties. PVDF can be prepared into a composite film that matches the size of the wound by the casting method, which lays the foundation for the composite film in the repair of soft tissue defects.

[0003] Potassium sodium niobate (KNN), a lead-free piezoelectric ceramic, has the advantages of excellent piezoelectric properties, good biocompatibility, and high mechanical quality factor. When KNN and PVDF are subjected to external forces, the crystals deform, the positive and negative charge centers of the crystals shift, and the positive and negative charges migrate to different ends, resulting in a potential difference between the two ends and thus forming an electric field. When the composite piezoelectric film is attached to the wound surface, the film deforms due to the movement of the body, and the electrical stimulation generated by the deformation is received by the cells to form electrical signals. After the Piezo protein on the cell membrane surface senses the electrical signal, it activates the calcium ion channel on the cell membrane surface, thereby increasing the calcium ion concentration in the cell and organelles. Calcineurin is activated by the higher calcium ion concentration, and through the relevant signal pathways, the transcription of the gene is regulated, which promotes the synthesis of transforming growth factor, and finally promotes the repair of large-area soft footprint defects. And KNN can be used as a nucleating agent to promote the polarization of PVDF and crystallize into a piezoelectric β phase. In addition, because KNN has excellent piezoelectric properties and a high piezoelectric coefficient, adding KNN nanoparticles to PVDF can improve the piezoelectric properties of the composite film. The composite film with good piezoelectric properties and biocompatibility can be used as an external electrical stimulus to enhance the bioelectric field effect to compensate for the endogenous electric field and accelerate the wound healing process. However, the traditional preparation method (such as physical vapor deposition and chemical vapor deposition) for preparing composite films with good biosafety has the constraints of expensive precision equipment and difficult removal of toxic byproducts. The present invention relates to the technology of preparing piezoelectric films by casting, which requires simple equipment, no toxic byproducts, good biosafety and processability. Therefore, the composite film preparation method designed by the present invention can achieve the purpose of constructing a tailor-made composite film biomimetic endogenous electric field to promote the repair of soft tissue defects.

[0004] The study found that domestic and foreign research mainly focused on improving the process parameters for preparing composite thin film materials, and no attempt was made to use this method to prepare the composite film and apply it to biological soft tissue repair treatment and explore the mechanism of the piezoelectric stimulation generated by the film on the internal signal pathway of cells. Summary of the invention

[0005] In order to fill the gap in the prior art in applying the composite film to biological soft tissue repair treatment and promoting the treatment of soft tissue defects, the present application proposes a potassium sodium niobate ceramic-based wound healing promoting film and a preparation method thereof.

[0006] The technical solution adopted by the present invention is:

[0007] A method for preparing a potassium sodium niobate ceramic-based wound healing-promoting film and a preparation method thereof, the preparation steps are as follows:

[0008] (1) synthesizing KNN precursor powder by ball milling, and then synthesizing KNN powder by calcination;

[0009] (2) PVDF powder and N,N-dimethylformamide solution were mixed and dispersed by ultrasonic, KNN powder was added to the solution, and KNN-PVDF composite film was prepared by tape casting.

[0010] The present invention provides a preparation method of a composite material, wherein the preparation steps of the KNN-PVDF composite film are as follows: the preparation steps of the KNN powder are as follows: sodium carbonate, potassium carbonate, niobium pentoxide, antimony trioxide, barium carbonate, bismuth oxide and zirconium oxide are taken through a calcination method to obtain KNN powder; the calcined powder is ball-milled with anhydrous ethanol as a ball-milling medium, and the KNN powder is obtained after centrifugal drying;

[0011] The present invention proposes an implementation method, PVD F / The N,N-dimethylformamide solution mixed solution comprises the following components by weight: 86-94 parts of N,N-dimethylformamide solution powder, 6-14 parts of PVDF powder, and 3-7 parts of KNN powder.

[0012] The PVD F The preparation method of the mixed solution of PVD / N,N-dimethylformamide solution is as follows: taking the composite film material component, F added to N,N-dimethylformamide solution was added to obtain a suspension, and then the ceramic powder passed through a 150-mesh sieve was added to the suspension, followed by tape casting using a scraper.

[0013] The present invention proposes an implementation mode, wherein the dispersion method is ultrasound and / or magnetic stirring, the ultrasonic dispersion time is 10-30 minutes, and the temperature is 10-40°C;

[0014] The present invention proposes an implementation mode, wherein the vacuum drying temperature is set to 50-80° C., and the drying time is 18-24 hours.

[0015] The present invention provides a method for preparing a composite film, wherein the prepared mixture is dripped onto a glass plate cleaned with anhydrous ethanol; and a scraper is used to prepare the composite film. The steps for preparing the composite film are: ultrasonic dispersion, uniform dripping of the solution onto a glass plate cleaned with anhydrous ethanol, and a 250-micron scraper are used to prepare the composite film. The formed film is placed in a 70°C oven and dried for 24 hours to obtain a composite film.

[0016] The present invention proposes an implementation mode, wherein the process parameters for preparing the film by the tape casting method are as follows: the scraper size is 250 microns, and the layer thickness is 0.1-0.2 mm.

[0017] The beneficial effects of the present invention are:

[0018] In the present invention, the film material of KNN and PVDF after tape casting obviously presents a classic peritectic structure, which indicates that the added powder forms a stable solid solution. KNN promotes the transformation of PVDF from α phase to β phase during the polarization process, improves the piezoelectric properties of PVDF, thereby promoting the improvement of the piezoelectric properties of the KNN / PVDF film, enhancing the potential of the exogenous electric field, and promoting the repair and treatment of soft tissue defects. KNN / PVDF is prepared into a composite film by tape casting, which improves the migration rate of fibroblasts and is conducive to adapting to the biological environment of skin defects. The composite film finally formed has good biocompatibility, excellent piezoelectric properties, and strong plasticity, which can solve the problem that large-area soft tissue defects are difficult to heal. It provides a new theoretical basis for the treatment of large-area soft tissue defects throughout the body. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 The scanning electron microscope images of the KNN / PVDF composite film in Example 1, (a) scanning electron microscope image of the PVDF film, (c) is a local enlarged image of (a), (b) scanning electron microscope image of the KNN / PVDF composite film, (d) is a local enlarged image of (b), indicating the successful synthesis of the KNN / PVDF composite film;

[0020] Figure 2 The X-ray diffraction spectra of the PVDF and KNN / PVDF films in Example 1 show that the film material to which 5% by mass of KNN-based ceramic powder is added clearly presents a classic peritectic structure, which indicates that the added powder has formed a stable solid solution without the presence of impurities;

[0021] Figure 3 The Fourier transform infrared spectra of PVDF and KNN / PVDF films in Example 1 show that the piezoelectric properties are improved after KNN is added to PVDF;

[0022] Figure 4 The electrograms of the scratch test of the PVDF and KNN / PVDF films co-cultured with fibroblasts in Example 1 show that the KNN / PVDF film can promote the migration of fibroblasts, thereby promoting wound healing;

[0023] Figure 5 The cytotoxicity test diagram of the PVDF and KNN / PVDF films prepared in Example 1 shows that the composite films have good biocompatibility. DETAILED DESCRIPTION

[0024] The specific implementation method of the present invention is further described below in conjunction with specific embodiments, but the described embodiments are only part of the embodiments of the present invention, and the content of the present invention is not limited thereto. Unless otherwise defined, the technical terms used in the following embodiments have the same meanings as those generally understood by technicians in the field to which the present invention belongs. The test reagents used in the following embodiments, unless otherwise specified, are all conventional biochemical reagents; the experimental methods, unless otherwise specified, are all conventional methods.

[0025] Example 1

[0026] (1) Sodium carbonate, potassium carbonate, niobium pentoxide, antimony trioxide, barium carbonate, bismuth oxide, and zirconium oxide powders were mixed at a rate of 0.96(K0.45Na0.55)(Nb0.97Sb0.03)O3–0.03Bi0.5(K0.15Na0.85)

[0027] 0.5ZrO3–0.01BaZrO3, stoichiometric ratio, weighed, of which sodium carbonate was 1g, the powder was ball-milled for 24 hours with anhydrous ethanol as the medium to make it fully mixed and dried, and the dried powder was sintered at 950°C for 5 hours at a heating rate of 5°C / min; after cooling, it was ground and passed through a 150-mesh sieve to obtain KNN powder. At 25°C, 1g of the prepared KNN was placed in an N,N-dimethylformamide solution containing 10% PVDF, in which the mass ratio of KNN was 5%.

[0028] (2) A thin film was formed on a glass plate by casting the solution onto a glass plate and heated until the solvent was completely evaporated to obtain a thin film, which was then polarized by corona polarization with a polarization electric field strength of 120 MV / m, a polarization temperature of 90°C, and a polarization time of 60 min. Finally, the polarization field strength was maintained at room temperature and the film was cut into pieces of 2 cm*2 cm in size.

[0029] In this example, a KNN / PVDF composite film prepared by a casting method was observed, and the results showed that there were no obvious defects and the film thickness was appropriate.

[0030] In this embodiment, the X-ray diffraction spectrum test revealed that the KNN / PVDF composite film had a classic peritectic structure, which indicated that the added powder had formed a stable solid solution without the presence of impurities.

[0031] In this embodiment, the Fourier infrared spectrum shows that after KNN is added to PVDF, the β-phase content of the material increases, and the composite film has good piezoelectric properties.

[0032] In this embodiment, the scratch test found that the KNN / PVDF composite film can promote the migration of fibroblasts, indicating that after KNN is added to PVDF, the composite film can promote the migration of cells.

[0033] In this embodiment, the biocompatibility test found that the KNN / PVDF composite film had no obvious toxicity to cells, showing good biocompatibility.

[0034] Example 2

[0035] (1) Sodium carbonate, potassium carbonate, niobium pentoxide, antimony trioxide, barium carbonate, bismuth oxide, and zirconium oxide powders were weighed according to the stoichiometric ratio of 0.96(K0.45Na0.55)(Nb0.97Sb0.03)O3–0.03Bi0.5(K0.15Na0.85)0.5ZrO3–0.01BaZrO3, wherein sodium carbonate was 0.8 g. The powders were ball-milled for 24 hours with anhydrous ethanol as the medium to make them fully mixed and dried. The dried powder was sintered at 950°C for 5 hours at a heating rate of 5°C / min. After cooling, it was ground and passed through a 150-mesh sieve to obtain KNN powder. 0.8 g of the prepared KNN was placed in an N,N-dimethylformamide solution containing 10% PVDF at 25°C, wherein the mass ratio of KNN was 4%.

[0036] (2) A thin film was formed on a glass plate by casting the solution onto a glass plate and heated until the solvent was completely evaporated to obtain a thin film, which was then polarized by corona polarization with a polarization electric field strength of 120 MV / m, a polarization temperature of 90°C, and a polarization time of 65 min. Finally, the polarization field strength was maintained at room temperature and the film was cut into pieces of 2 cm*2 cm in size.

[0037] In this example, a KNN / PVDF composite film prepared by a casting method was observed, and the results showed that there were no obvious defects and the film thickness was appropriate.

[0038] In this embodiment, the X-ray diffraction spectrum test revealed that the KNN / PVDF composite film had a classic peritectic structure, which indicated that the added powder had formed a stable solid solution without the presence of impurities.

[0039] In this embodiment, the Fourier infrared spectrum shows that after KNN is added to PVDF, the β-phase content of the material increases, and the composite film has good piezoelectric properties.

[0040] In this embodiment, the scratch test found that the KNN / PVDF composite film can promote the migration of fibroblasts, indicating that after KNN is added to PVDF, the composite film can promote the migration of cells.

[0041] In this embodiment, the biocompatibility test found that the KNN / PVDF composite film had no obvious toxicity to cells, showing good biocompatibility.

[0042] Example 3

[0043] (2) Sodium carbonate, potassium carbonate, niobium pentoxide, antimony trioxide, barium carbonate, bismuth oxide, and zirconium oxide powders were mixed at a rate of 0.96(K0.45Na0.55)(Nb0.97Sb0.03)O3–0.03Bi0.5(K0.15Na0.85)

[0044] 0.5ZrO3–0.01BaZrO3, stoichiometric ratio was weighed, of which sodium carbonate was 0.6g, and the powder was ball-milled for 24 hours with anhydrous ethanol as the medium to make it fully mixed and dried, and the powder obtained after drying was sintered at 900℃ for 5h, with a heating rate of 8℃ / min; after cooling, it was ground and passed through a 150-mesh sieve to obtain KNN powder. At 25℃, 0.8g of the prepared KNN was placed in an N,N-dimethylformamide solution containing 10% PVDF, in which the mass ratio of KNN was 3%.

[0045] (2) A thin film was formed on a glass plate by casting the solution onto a glass plate and heated until the solvent was completely evaporated to obtain a thin film, which was then polarized by corona polarization with a polarization electric field strength of 120 MV / m, a polarization temperature of 90°C, and a polarization time of 65 min. Finally, the polarization field strength was maintained at room temperature and the film was cut into pieces of 2 cm*2 cm in size.

[0046] In this example, a KNN / PVDF composite film prepared by a casting method was observed, and the results showed that there were no obvious defects and the film thickness was appropriate.

[0047] In this embodiment, the X-ray diffraction spectrum test revealed that the KNN / PVDF composite film had a classic peritectic structure, which indicated that the added powder had formed a stable solid solution without the presence of impurities.

[0048] In this embodiment, the Fourier infrared spectrum shows that after KNN is added to PVDF, the β-phase content of the material increases, and the composite film has good piezoelectric properties.

[0049] In this embodiment, the scratch test found that the KNN / PVDF composite film can promote the migration of fibroblasts, indicating that after KNN is added to PVDF, the composite film can promote the migration of cells.

[0050] In this embodiment, the biocompatibility test found that the KNN / PVDF composite film had no obvious toxicity to cells, showing good biocompatibility.

[0051] Comparative Example 1

[0052] (1) Dissolve 10g of PVDF powder in 90g of N,N-dimethylformamide solution so that the mass ratio of PVDF is 10%. Form a film on a glass plate by casting, cast the solution onto the glass plate, heat until the solvent is completely volatilized, obtain a film, and then polarize it by corona polarization, with a polarization electric field strength of 120MV / m, a polarization temperature of 90°C, and a polarization time of 65min. Finally, maintain the polarization field strength to room temperature, and cut the film into 2cm*2cm sizes.

[0053] In this example, a PVDF film prepared by a casting method was observed, and the results showed that there were no obvious defects and the film thickness was appropriate.

[0054] In this embodiment, the X-ray diffraction spectrum test revealed that the PVDF film had a classic crystalline structure, which indicated that the film was successfully prepared without the presence of impurities.

[0055] In this embodiment, according to the Fourier infrared spectrum, the β-phase content of PVDF is low and it has certain piezoelectric properties.

[0056] In this embodiment, the scratch test found that the PVDF film can promote the migration of fibroblasts to a certain extent, but the promotion ability is limited, and the composite film can partially promote the migration of cells.

[0057] In this embodiment, the biocompatibility test found that the PVDF film had no obvious toxicity to cells, showing good biocompatibility.

[0058] Comparative Example 2

[0059] (1) 8g of PVDF powder was dissolved in 72g of N,N-dimethylformamide solution so that the mass ratio of PVDF was 10%. A film was formed on a glass plate by casting, and the solution was cast on the glass plate. The film was heated until the solvent was completely volatilized to obtain a film, and then polarized by corona polarization with a polarization electric field strength of 120MV / m, a polarization temperature of 90°C, and a polarization time of 60min. Finally, the polarization field strength was maintained at room temperature, and the film was cut into 2cm*2cm sizes.

[0060] In this example, a PVDF film prepared by a casting method was observed, and the results showed that there were no obvious defects and the film thickness was appropriate.

[0061] In this embodiment, the X-ray diffraction spectrum test revealed that the PVDF film had a classic crystalline structure, which indicated that the film was successfully prepared without the presence of impurities.

[0062] In this embodiment, according to the Fourier infrared spectrum, the β-phase content of PVDF is low and it has certain piezoelectric properties.

[0063] In this embodiment, the scratch test found that the PVDF film can promote the migration of fibroblasts to a certain extent, but the promotion ability is limited, and the composite film can partially promote the migration of cells.

[0064] In this embodiment, the biocompatibility test found that the PVDF film had no obvious toxicity to cells, showing good biocompatibility.

[0065] Comparative Example 3

[0066] (1) 9g of PVDF powder was dissolved in 81g of N,N-dimethylformamide solution so that the mass ratio of PVDF was 10%. A film was formed on a glass plate by casting, and the solution was cast onto the glass plate. The film was heated until the solvent was completely volatilized to obtain a film, and then polarized by corona polarization with a polarization electric field strength of 120MV / m, a polarization temperature of 90°C, and a polarization time of 65min. Finally, the polarization field strength was maintained at room temperature, and the film was cut into 2cm*2cm sizes.

[0067] In this example, a PVDF film prepared by a casting method was observed, and the results showed that there were no obvious defects and the film thickness was appropriate.

[0068] In this embodiment, the X-ray diffraction spectrum test revealed that the PVDF composite film had a classic crystalline structure, which indicated that the film was successfully prepared without the presence of impurities.

[0069] In this embodiment, according to the Fourier infrared spectrum, the β-phase content of PVDF is low and it has certain piezoelectric properties.

[0070] In this embodiment, the scratch test found that the PVDF film can promote the migration of fibroblasts to a certain extent, but the promotion ability is limited, and the composite film can partially promote the migration of cells.

[0071] In this embodiment, the biocompatibility test found that the PVDF film had no obvious toxicity to cells, showing good biocompatibility.

[0072] The above embodiments and comparative examples are only used to illustrate the technical solutions of the present invention, rather than to limit them. Although the invention has been described in detail with reference to the aforementioned embodiments and comparative examples, a person skilled in the art should understand that the technical solutions described in the aforementioned examples can still be modified, or some of the technical features can be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the various examples of the present invention.

Claims

1. A potassium sodium niobate ceramic-based wound healing film and a preparation method thereof, the preparation steps are as follows: (1) synthesizing potassium sodium niobate precursor powder by ball milling, vacuum drying, and then synthesizing potassium sodium niobate powder by calcination; (2) PVDF powder and N,N-dimethylformamide solution were mixed and dispersed by ultrasonic, KNN powder was added to the solution, and KNN-PVDF composite film was prepared by tape casting.

2. The method for preparing a potassium sodium niobate ceramic-based wound healing film and a preparation method thereof according to claim 1, characterized in that: The preparation steps of the KNN powder are as follows: sodium carbonate, potassium carbonate, niobium pentoxide, antimony trioxide, barium carbonate, bismuth oxide and zirconium oxide are taken through calcination to obtain KNN powder; the calcined powder is ball-milled with anhydrous ethanol as a ball-milling medium, and the KNN powder is obtained after centrifugal drying.

3. The method for preparing a potassium sodium niobate ceramic-based wound healing film and a preparation method thereof according to claim 1, characterized in that: The PVDF / N,N-dimethylformamide solution mixed solution comprises the following components by weight: 86-94 parts of N,N-dimethylformamide solution powder, 6-14 parts of PVDF powder, and 3-7 parts of KNN powder.

4. A method for preparing a potassium sodium niobate ceramic-based wound healing film and a preparation method thereof according to claim 3, characterized in that: The PVDF / N,N-dimethylformamide solution mixed solution is prepared by taking the composite film material component, adding PVDF to N,N-dimethylformamide solution to obtain a suspension, then adding KNN powder after passing through a 150-mesh sieve to the suspension, and then using a scraper for tape casting.

5. The method for preparing a potassium sodium niobate ceramic-based wound healing promoting film and a preparation method thereof according to claim 1, characterized in that: The dispersion method is ultrasonic dispersion, the time is 10-30 minutes, and the temperature is 10-40°C.

6. The method for preparing a potassium sodium niobate ceramic-based wound healing promoting film and a preparation method thereof according to claim 1, characterized in that: The vacuum drying temperature is set at 50-80°C and the drying time is 18-24h.

7. The method for preparing a potassium sodium niobate ceramic-based wound healing promoting film and a preparation method thereof according to claim 4, characterized in that: The prepared mixture was dropped onto a glass plate cleaned with anhydrous ethanol; a composite film was prepared using a scraper. The steps of preparing the composite film are as follows: ultrasonic dispersion, uniformly dripping the solution onto a glass plate cleaned with anhydrous ethanol, using a 250-micron scraper to prepare the composite film, and placing the formed film in a 70° C. oven to dry for 24 hours to obtain the composite film.

8. The method for preparing a potassium sodium niobate ceramic-based wound healing promoting film and a preparation method thereof according to claim 7, characterized in that: The process parameters for preparing the film by tape casting were as follows: the blade size was 250 μm and the layer thickness was 0.1-0.2 mm.